Mechanical properties of AC4CH alloys produced by heated mould continuous casting process. (June 2013) - Okayasu, M; Takeuchi, S; Ohkura, Y; Shiraishi, T
Abstract : This paper reports an investigation of the mechanical properties of cast aluminium AC4CH alloys produced by a unique casting method known as the heated mould continuous casting (OCC) process. The tensile and fatigue strengths and material ductility of the OCC samples are much higher than that for the same alloy produced by conventional gravity casting. The high tensile and high fatigue strengths of the OCC samples are reflected by the presence of tiny round α -Al grains, and the high ductility of OCC is a result of the regularly organized crystal orientation.